(untitled) (International Journal of Engineering and Computer Science, 2018)
Sensors in a wireless sensor network (WSN) are prone to failure, due to the energy depletion, hardware failures, etc. Fault tolerance is one of the critical issues in WSNs. The existing fault tolerance mechanisms either consume significant extra energy to detect and recover from the failures or need to use additional hardware and software resource. In this paper, we propose a novel energy-aware fault tolerance mechanism for WSN, called Informer Homed Routing (IHR). In our IHR, non cluster head (NCH) nodes select a limited number of targets in the data transmission. Therefore it consumes less energy. In this paper, we propose an agreement-based fault detection and recovery protocol for cluster head (CH) in wireless sensor networks (WSNs). The aim of protocol is to accurately detect CH failure to avoid unnecessary energy consumption caused by a mistaken detection process. Our experimental results show that our proposed protocol can significantly reduce energy consumption, compared to two existing protocols: Low-Energy Adaptive Clustering Hierarchy (LEACH) and Dual Homed Routing (DHR).